Antarctic Travel Writing and the Problematics of the Pristine: Two Australian Novelists' Narratives of Tourist Voyages to Antarctica - Elizabeth Leane (2012)
With the increasing popularity of Antarctic tourism in the last decade or so, new narratives of Antarctic encounter have begun to appear: narratives that attempt to understand how the individual traveller might relate to the continent and all it has come to symbolise. These texts,which as a group can be classed as Antarctic travel writing, differ from polar exploration narratives and from accounts of life at Antarctic bases, because their authors can be identified as tourists. Antarctic travel writing includes full-length books, such as Sara Wheeler’s Terra Incognita , Jenny Diski’s Skating to Antarctica and Peter Matthiessen’s End of the Earth , and also essays and feature articles in the media. The aim of this article is to examine two examples of this new genre of Antarctic travel writing published in the Australian media. Both are feature articles by established Australian novelists (Helen Garner and Thomas Keneally) describing tourist trips to Antarctica, and both appeared in the Age newspaper’s Good Weekend magazine. Each article can be read as an exploration of the anxieties of the writer-cum-tourist entering an environment which has become synonymous, in the public imagination, with ‘pristine nature.’ Both Garner and Keneally are concerned with maintaining the ‘pristine’ quality of the continent, with protecting it from anything that threatens to alter its original state. Each writer, however,has a very different idea of what this state comprises.